Lesniowski-Crohn disease and colon cancer - Jankowski, Michał; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2006)
Non-specific, granulomatous inflammation of the colon called Lesniowski-Crohn disease is one of the chronic illnesses predisposing to the large intestine cancer. The prevalence of this disease increases in proportion with civilization progress of the society. The etiology of the disease has not been recognized in detail, the prevailing opinion is that it is a result of the series of factors: heterogeneous and genetic. The research published with participation of patients is not abounding, however, it suggests that the risk of falling ill with cancer of the large intestine, its outlook and a 5-year survival do not significantly differ from the results achieved in patients with ulcerative colitis. An unambiguous treatment and supervision model within the scope of prevention of the cancer of the large intestine in patients with Lesniowski Crohn disease have not been worked out yet. However, it seems that for an early detection of displasia and cancer it is significant to carry out colonoscopy, chromoendoscopy with collection of numerous biopsies. An increased prevalence of cancer of the large intestine and Lesniowski-Crohn disease may contribute to the necessity of working out an algorithm of procedures for these patients. However, most often, detection of cancer of the large intestine in patients with Lesniowski-Crohn disease is unintentional and thus is a challenge for the modern diagnostics of the inflammatory diseases of the large intestine.